A pH/temperature responsive nanocomposite for chemo-photothermal synergistic cancer therapy - Mustafa Rawand A.; Ran Meixin; Wang Yonghui; Yan Jiaqi; Zhang Yu; Rosenholm Jessica M.; Zhang Hongbo (KeAi Communications Co., 2025)
To optimize synergistic breast cancer treatment, a nanocomposite was fabricated with pH-temperature responsive and chemo-photothermal combination therapy. Herein, gold nanorods (AuNRs) are coated with [poly[(N-isopropylacrylamide)-co-(methacrylic acid)] (p(NIPAM-co-MAA)) modified mesoporous silica (MS) for Doxorubicin (DOX) delivery (AuNR@DOX-MS@p(NIPAM-co-MAA)). Upon NIR radiation, the AuNR core induced hyperthermia via generating heat. Simultaneously, the polymer layer collapsed in response to high temperature/low pH, which allowed the triggering of DOX release from the MS shell at the tumor site. With this nanocomposite, nearly zero premature release of DOX at physiological pH/temperature was detected, while effective DOX release was reported at higher temperature/lower pH values. In addition, in vitro studies demonstrated that the nanocomposite has a substantial uptake efficiency of MDA-MB-231 breast cancer cells, with a significant increase in suppressing MDA-MB-231 ​cell proliferation in response to laser irradiation. The in vivo experiments further verified the high efficiency of the fabricated nanocomposite in accumulating at the tumor site and the good capability in suppressing tumor growth in the mice upon intravenous injection, while exhibiting good biosafety in relation to major organs in the body. Thus, the synthesized nanocomposite could be a potential nanocarrier for breast cancer treatment with synergistic chemo-photothermal therapeutic capability.